A challenging diagnosis: Case report of oral metastasis from gastric adenocarcinoma mimicking pyogenic granuloma. Issue 13 (March 2018) - Soares, Ciro Dantas; Rocha, Breno Amaral; Paranaiba, Lívia Máris Ribeiro; de Melo-Filho, Mário Rodrigues; Jorge, Jacks; de Carvalho, Maria Goretti Freire; de Almeida, Oslei Paes
Abstract: Rationale: Oral metastases occur more commonly in bone, but can also manifest in soft tissues and eventually resemble a reactive lesion. Few cases of oral metastases mimicking reactive lesions in soft tissues have been reported to date. Patient concerns: We report a metastasis of gastric carcinoma (GC) to the oral mucosa without bone involvement in a 43 yom clinically and microscopically mimicking a reactive lesion. The patient related that the lesion had 1 month of evolution, and the ulcerated area suggested the lesion was related to trauma. Diagnoses: The histopathological examination of the lesion revealed an exuberant granulation tissue with few neoplastic cells, and the initial diagnosis of pyogenic granuloma was considered. In a second analysis, clusters of clear cells morphologically similar to degenerating mucous cells or macrophages, positive for Cytokeratin (CK)-20, and CDX2 were found. At the moment, it was confirmed the presence of a primary GC in the patient. Interventions: A palliative radiotherapy/chemotherapy was started. Outcomes: However, the patient died 3 months after the diagnosis of oral metastasis. Lessons: This report highlights the importance of careful clinical and microscopic examinations in cases of oral metastasis that may mimic a reactive lesion.